INFLUENCE OF Momordica charantia (L.) ON THE PHARMACOKINETICS AND PHARMACODYNAMICS OF GLICLAZIDE IN ALLOXAN-INDUCED DIABETIC RATS - Tubagus Akmal; Lucy Sasongko (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Diabetes mellitus is a metabolic disorder present in the top ten diseases that cause death. Diabetes treatment usually uses conventional drugs, such as gliclazide, which is the first choice in patients with type 2 diabetes mellitus who are intolerant to metformin. In addition to conventional medicine, herbal medicines are in great demand and have become a focus of research to obtain an alternative treatment for type 2 diabetes mellitus. One herb that has been widely used and studied is the bitter melon. This study aimed to determine the effects of bitter melon extract (BME) on the pharmacokinetics and pharmacodynamics of gliclazide when used simultaneously. The study was conducted on three groups of rats with alloxan-induced diabetes. Group 1 received a single dose of gliclazide (33 mg/kg BW, n = 3), group 2 received aqueous extracts of bitter melon fruit (341 mg/kg BW, n = 4), and group 3 received a combination of gliclazide and an aqueous extract of bitter melon (n = 4). The pharmacokinetic profile of gliclazide is affected by BME, where interactions occur during the absorption phase. The blood glucose levels were measured using a glucometer. Decreased blood glucose levels following administration of gliclazide, extract of bitter melon, and a combination of gliclazide and extract of bitter melon 6 hours after dosing were 74.73%, 82.977%, and 86.457%, respectively. This study demonstrated the interactions between gliclazide and BME in the absorption phase of gliclazide and its effect on blood glucose levels.